Exploring Accountability and Transparency in Government Agency Management: A Literature Review - Irawati, Syati; Hayat, Atma; Juniar, Asrid; Handayani, Sri Astuti (Yayasan Sinergi Kawula Muda, 2024)
Public bureaucratic practices are frequently criticized for being impolite, unfriendly, discriminatory, and for having service systems that are non-transparent, complicated, and do not guarantee certainty in terms of time and costs. These issues arise from a lack of transparency and accountability in public service implementation. Transparency involves the freedom to access information, while accountability ensures that activities are carried out responsibly and answerable to the public. This research explores the relationship between accountability and transparency in government agency management through a literature review. The study analyzes 30 journals from state and private universities, published between 2018 and 2023, to understand their impact on government performance. Data was collected from Google Scholar using the keywords